Government Intervention in Price Regulation: A Sharia Review of Afghanistan’s Pricing Policy After 2021 - Abdullah Farooqi; Nur'aini (Al-Mustashfa: Jurnal Penelitian Hukum Ekonomi Syariah, 2026)
Afghanistan’s political transition in August 2021 generated severe economic disruption, weakened household purchasing power, and increased vulnerability to food insecurity and market instability. This study aims to evaluate government intervention in Afghanistan’s post-2021 pricing policy through the principles of tasʿīr, ḥisbah, and maqāṣid al-sharīʿah, with particular attention to market fairness and public welfare. The study employs normative qualitative legal research combined with statutory, conceptual, and policy approaches. Data were collected through documentary analysis of Afghan government regulations, ministerial policies, official reports, international institutional publications, classical Islamic legal works, and recent academic studies. The findings show that Afghanistan’s pricing policy does not primarily operate through comprehensive compulsory price fixing but through a mixed model of corrective market regulation, including market inspections, reductions in import-related costs, trade facilitation, consumer protection, and control of unsafe or unfair commercial practices. These measures are broadly consistent with Islamic economic law when they respond to genuine market failure, are implemented proportionately, protect both traders and consumers, and contribute to ḥifẓ al-nafs and ḥifẓ al-māl. However, their contribution to public welfare remains limited by unemployment, weak household income, declining international assistance, fragile financial institutions, and persistent food insecurity. This study contributes a Sharia-based policy-evaluation framework that distinguishes arbitrary price fixing from legitimate corrective market intervention in a fragile post-conflict economy.